(untitled) (Marketing Journal, 2026)
This article studies the experience of improving the use of the marketing concept in the textile industry. Market segmentation is the process of dividing consumers and sellers of textile products into segments in the market, distinguished by their requirem ents and reactions. Also, in Uzbekistan, some scientists, studying the issue of marketing concepts in the textile industry as part of their scientific work, have partially addressed this issue in the process of developing marketing concepts and studying th e difficulties in this process.